2010
DOI: 10.1093/ndt/gfq517
|View full text |Cite
|
Sign up to set email alerts
|

Successful transplantation of a donor kidney with diffuse proliferative lupus nephritis and crescents--a case report

Abstract: Pre-existing diffuse proliferative glomerulonephritis (DPGN) in a potential deceased kidney donor has been considered a contraindication for transplantation. We report a case of a patient who underwent a successful deceased donor renal transplantation from a donor with history of systemic lupus erythematosus (SLE) whose baseline biopsy revealed DPGN. Although the histology was relatively benign in the procurement kidney biopsy done by frozen section, the final light microscopy available after transplantation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Finally, other histological lesions have been described in zero-time biopsies, like giant mitochondria 39 and donor glomerular pathology [40][41][42][43][44][45][46] . As these pre-existing conditions are very rare, guidance on the interpretation and implications of these findings only comes from individual case reports, and no general conclusions can be made.…”
Section: Histological Grading Of Individual Lesionsmentioning
confidence: 99%
“…Finally, other histological lesions have been described in zero-time biopsies, like giant mitochondria 39 and donor glomerular pathology [40][41][42][43][44][45][46] . As these pre-existing conditions are very rare, guidance on the interpretation and implications of these findings only comes from individual case reports, and no general conclusions can be made.…”
Section: Histological Grading Of Individual Lesionsmentioning
confidence: 99%
“… 47 , 55 Few reports in the literature involving inadvertent transplantation of lupus kidneys to recipients without lupus showed that subendothelial immune complexes progressively decreased in intensity but were still detectable by light and immunofluorescence microscopy 6-8 months after kidney transplantation. 62 , 63 , 64 , 65 Subendothelial immune complexes disappeared from the kidney biopsies beyond 12 months. Interestingly, subepithelial deposits lasted much longer and were detectable by light microscopy and immunofluorescence microscopy even 3-5 years after transplantation.…”
Section: The Post-therapy Kidney Biopsy: Histological Response Therap...mentioning
confidence: 95%
“…Interestingly, subepithelial deposits lasted much longer and were detectable by light microscopy and immunofluorescence microscopy even 3-5 years after transplantation. 64 , 66 , 67 , 68 Electron microscopy may differentiate “new” from “old” subepithelial immune complex deposits in repeat kidney biopsies. New deposits are dense and found in the subepithelial space, while progressively older deposits migrate through the glomerular basement layers to the subendothelial space.…”
Section: The Post-therapy Kidney Biopsy: Histological Response Therap...mentioning
confidence: 99%